The Impact of Loneliness on Stress in Highly Educated Unemployed Housewives Post-Marriage: Social Support as a Moderator - Saraswaty, Ravina; Wulandari, Maria Theresia Asti (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Individuals with higher educational backgrounds often hold higher standards in evaluating social relationships, making them more vulnerable to isolation when intellectual and emotional support is lacking. Objective: This study aims to examine the effect of loneliness on stress among highly educated, non-working housewives and to explore the moderating role of social support. Method: A non-experimental cross-sectional design was used with a non-probability convenience sampling technique. Participants were housewives aged 25–40. Data were collected using validated questionnaires: MSPSS, UCLA Loneliness Scale (Version 3), and PSS-10. Results: Loneliness showed a positive significant relationship with stress, indicating higher loneliness correlates with higher stress. The regression coefficient for social support in relation to stress was significantly positive, meanwhile social support negatively correlated with loneliness but did not significantly affect stress or moderate the relationship between loneliness and stress. Conclusion: The study concludes that loneliness significantly contributes to increased stress, while social support does not significantly reduce stress, possibly due to other moderating factors like relationship quality or personality traits. Abstrak Latar belakang: Individu dengan pendidikan tinggi cenderung memiliki standar tinggi dalam menjalin relasi sosial, sehingga lebih rentan mengalami isolasi saat dukungan intelektual dan emosional kurang. Tujuan: Meneliti pengaruh kesepian terhadap stres pada ibu rumah tangga berpendidikan tinggi yang tidak bekerja, serta mengeksplorasi peran moderasi dukungan sosial. Metode: Penelitian kuantitatif dengan desain potong lintang dan teknik convenience sampling. Partisipan adalah ibu rumah tangga usia 25–40 tahun, minimal lulusan diploma, tidak bekerja atau berhenti bekerja setelah menikah, hanya mengurus rumah tangga, telah menikah minimal tiga tahun, dan memiliki pengalaman kerja minimal satu tahun. Instrumen yang digunakan yaitu MSPSS, UCLA Loneliness Scale versi 3, dan PSS-10. Hasil: Kesepian berhubungan positif dan signifikan dengan stres, menunjukkan semakin tinggi kesepian, semakin tinggi stres. Dukungan sosial berkorelasi negatif dengan kesepian, tetapi tidak berpengaruh signifikan terhadap stres maupun memoderasi hubungan kesepian dan stres. Kesimpulan: Kesepian berkontribusi signifikan terhadap stres, sementara dukungan sosial tidak berperan sebagai pelindung, kemungkinan dipengaruhi oleh faktor lain seperti kualitas hubungan atau kepribadian.